Local knowledge of gully erosion in Kinshasa, Democratic Republic of Congo: the case of the avenue sikama mega-gully in the commune of Kisenso - Kouagou Raoul, Sambieni; Pika Léa, Mukubu; Alioune Badara, Diop; Imwangana Fils, Makanzu; Jan, Bogaert (Revue Ecosystèmes et Paysages, 2024)
One of the current environmental challenges facing tropical cities is the sustainable management of gully erosion. Indeed, gully erosion in a built-up environment causes the loss of infrastructures, homes and human lives. This has devastating socio-economic and socio-psychological effects. This study analyses the local knowledge around the Avenue Sikama mega-gully in Kisenso, one of Kinshasa's municipalities, about the gullies according to the zone of location in relation to the gully (upstream zone, critical zone, downstream zone). Surveys were carried out with a random sample of 82 respondents in each of the three zones considered, covering the causes of erosion, erosion control proposals, and assessment of perceived level of risk exposure (nr) on an increasing scale from 1 to 10. The contingency tables of causes and control proposals for the three zones considered were subjected to correspondence factorial analysis, and the nr data to analysis of variance. In the upstream and downstream zones, respondents rated their risk as medium (nr = 4.3 and nr = 5.2 respectively). In the upstream zone, they cited technical and financial causes, and proposed plot management, while in the downstream zone, they cited a lack of community spirit as a cause, and proposed community mobilization. In the critical zone, respondents rated their risk as high (nr = 9.6). They cited the lack of spatial organization as the cause and called for help. Local knowledge of erosion therefore remains calibrated not by the landscape perspective of the problem but by the local experience of the immediate environment.